On the structural evolutionary behavior of the CdTe/HgCdTe interface during the annealing process - Jiyuan Chen; Yang Lin; Lu Li; Xiao Wang; Wei Dong; Li Liu; Zhentao Yuan; Xiaoying Cui; Shouzhang Yuan (Journal of Materials Research and Technology, 2024)
In this study, secondary ion mass spectrometry and a semiconductor parameter analyzer were used to study and analyze the component interdiffusion at the CdTe/HgCdTe interface before and after annealing, as well as the effect of the formation of a gradient bandgap layer from annealing on the electrical properties of the metal–insulator-semiconductor (MIS) structure. The site-direction relationship of the contracted crystals at the CdTe/HgCdTe interface was revealed by transmission electron microscopy, and it was found that the stacking dislocations in the CdTe layer were significantly reduced after annealing and that the Hg atoms diffused into the CdTe layer through the high-temperature annealing and occupied the lattice positions of the Cd atoms, thus forming the HgCdTe structure, which formed a contracted-crystalline structure with the CdTe substrate. Molecular dynamics was applied to simulate the specific atomic diffusion behavior at different temperatures and different times during the high temperature annealing process, and the above experimental results were verified by a research note on the variation of the diffusion phenomena during the process.